2013
DOI: 10.1146/annurev-anthro-092412-155558
|View full text |Cite
|
Sign up to set email alerts
|

The Nature/Culture of Genetic Facts

Abstract: This review aims to explore the relationship between anthropology and genetics, an intellectual zone that has been occupied in different ways over the past century. One way to think about it is to contrast a classical "anthropological genetics" (Roberts 1965), that is to say, a genetics that presumably informs anthropological issues or questions, with a "genomic anthropology" (Pálsson 2008), that is to say, an anthropology that complements and relativizes modern genomics (on the model of, say, medical anthropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 166 publications
0
25
0
Order By: Relevance
“…Through the lens of winemaking, it tracks how wine production also mediates a collective indigenous identity and helps to establish a historical imaginary that underpins the modern nation state, and consequently forms part of broader processes which naturalize a Jewish presence. This work, therefore, speaks to conversations in the anthropology of nature and to science and technology studies pertaining to the production of indigenous belonging (Comaroff & Comaroff 2009;Kravel-Tovi 2015;Marks 2013;Seeman 2010;Weiss 2004).…”
Section: Indigenous Winementioning
confidence: 95%
“…Through the lens of winemaking, it tracks how wine production also mediates a collective indigenous identity and helps to establish a historical imaginary that underpins the modern nation state, and consequently forms part of broader processes which naturalize a Jewish presence. This work, therefore, speaks to conversations in the anthropology of nature and to science and technology studies pertaining to the production of indigenous belonging (Comaroff & Comaroff 2009;Kravel-Tovi 2015;Marks 2013;Seeman 2010;Weiss 2004).…”
Section: Indigenous Winementioning
confidence: 95%
“…Articles in this journal have repeatedly shown that science educators and students are interested in, feed on, and contribute to theoretical considerations when conveyed at an appropriate level of complexity. There is a wealth of contributions the discussion of which would certainly strengthen and broaden the perspective of this book and would encourage readers to think along these lines on issues such as gender or human sexuality (see, e.g., Fuentes 2012; Goodman and Leatherman 1998;Goodman et al 2003;Marks 2013a;Mukhopadhyay and Moses 1997).…”
Section: Some Concluding Thoughtsmentioning
confidence: 99%
“…A deme can only be defined and is not something as real as an Aristotelian Individual (Ghiselin, 1997). Similarly, groupings found as clusters of genes (Spencer, 2015), depends on which genes are investigated and most studies have been chosen to be geographically diverse and hence divergent (Marks, 2013). Admixture from past demes of archaic hominins such as Neanderthals, Denisovans and an unknown ancient African genetic ancestor, could be used to partition humans into groups, such as two groups of Sub-Saharan Africans, versus all non-Africans from an early Neanderthal introgression, and then an extra derived group of Denisovan Asio-Melanesians (Sankararaman et al, 2016;Vernot et al, 2016;Hsieh et al, 2016).…”
Section: Figure 14a and 14b Race-ideology Supporting Personal And Instimentioning
confidence: 99%